2005
DOI: 10.1111/j.1365-2672.2004.02521.x
|View full text |Cite
|
Sign up to set email alerts
|

A beta-glucosidase gene isolated from wine Lactobacillus plantarum is regulated by abiotic stresses

Abstract: Aims: Little genetic information exists on the ability of wine lactic acid bacteria (LAB) to hydrolyse glycoconjugates during malolactic fermentation. We tried to fill this important gap by characterizing a gene codifying for a putative b-glucosidase enzyme from wine Lactobacillus plantarum and from a commercial strain of Oenococcus oeni. Methods and Results:The coding region of the putative b-glucosidase gene is 1400 nucleotides long and started with an ATG codon. The gene is widespread among LAB and the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 23 publications
1
67
1
Order By: Relevance
“…Some Lactobacillus species have also displayed the ability to survive the harsh wine conditions (G-Alegría et al, 2004;Pozo-Bayón et al, 2005), of which the species Lactobacillus plantarum has shown the most potential as a starter culture (for review see Du and a commercial culture has recently been released by Lallemand as Lactobacillus plantarum V22 ® (Bou & Krieger, 2004;Fumi et al, 2010). This species of Lactobacillus also shows a more diverse enzymatic profile than O. oeni (Matthews et al, 2004;Spano et al, 2005;Mtshali et al, 2010), which could play an important role in the modification of the wine aroma profile (Guerzoni et al, 1995;Swiegers et al, 2005;Matthews et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some Lactobacillus species have also displayed the ability to survive the harsh wine conditions (G-Alegría et al, 2004;Pozo-Bayón et al, 2005), of which the species Lactobacillus plantarum has shown the most potential as a starter culture (for review see Du and a commercial culture has recently been released by Lallemand as Lactobacillus plantarum V22 ® (Bou & Krieger, 2004;Fumi et al, 2010). This species of Lactobacillus also shows a more diverse enzymatic profile than O. oeni (Matthews et al, 2004;Spano et al, 2005;Mtshali et al, 2010), which could play an important role in the modification of the wine aroma profile (Guerzoni et al, 1995;Swiegers et al, 2005;Matthews et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…rhamnosidases. Based on their adaptation to the harsh wine milieu and their general hydrolytic abilities toward different glycosides (16,17,50), wine-related lactic acid bacteria (LAB) have attracted much interest as a potential source of novel glycosidases (34).Consequently, several (intracellular) glycosidases from different wine-related bacterial species have already been identified and characterized (11,12,(36)(37)(38)48). Another driving force for the identification and characterization of bacterial glycosidases, including rhamnosidases, is the observation that plant secondary metabolites (i.e., flavonoids) with potential health benefits have improved bioavailability in their aglycon forms (26).…”
mentioning
confidence: 99%
“…Consequently, several (intracellular) glycosidases from different wine-related bacterial species have already been identified and characterized (11,12,(36)(37)(38)48). Another driving force for the identification and characterization of bacterial glycosidases, including rhamnosidases, is the observation that plant secondary metabolites (i.e., flavonoids) with potential health benefits have improved bioavailability in their aglycon forms (26).…”
mentioning
confidence: 99%
“…βG activity in O. oeni, the main bacterial species conducting MLF, was confirmed more than 20 years ago (Guilloux-Benatier et al, 1993). Over the past decades, numerous investigations have been conducted, providing evidence for the potential βG activity of O. oeni strains for flavor enhancement in wines (Spano et al, 2005;Michlmayr et al, 2010;Gagné et al, 2011). It has been reported that the possession of glycosidic activities is widespread and strain dependent among O. oeni strains (Barbagallo et al, 2004;Grimaldi et al, 2005;Saguir et al, 2009).…”
mentioning
confidence: 99%